Study on a cooperative MAC protocol with priority-based contention for wireless networks - LIU Yun; LIU Kai; ZENG Feng (Tongxin xuebao)
A cooperative medium access control protocol with priority-based contention（PBC-CMAC） was presented for wireless networks.In the protocol,a source node preselected two optimal relays from its local relay information table,and set their priorities in cooperative request-to-send（CRTS） packet based on the relay efficiency,which reflects the de-gree of its saved transmission time.Through overhearing the handshakes between the source node and destination node,the two candidate relays can obtain instantaneous transmission rate among source node,destination node and themselves,and then contend to be the final relay without contention collisions according to their priorities and rate information.The proposed protocol can rapidly select the optimal relay to cooperatively transmit data packets under current channel qual-ity without contention collisions from all the potential relays,increase the successful probability of relay selection and cooperation efficiency,and then improve multiple access performance.Simulation results show that the proposed proto-col outperforms IEEE 802.11 request-to-send/clear-to-send（RTS/CTS） and CoopMAC protocols.